Inhibitory Effect of Multivalent Rhamnobiosides on Recombinant Horseshoe Crab Plasma Lectin Interactions with Pseudomonas aeruginosa PAO1. Issue 23 (3rd November 2016) - Herczeg, Mihály; Mező, Erika; Molnár, Nikolett; Ng, Sim‐Kun; Lee, Yuan‐Chuan; Dah‐Tsyr Chang, Margaret; Borbás, Anikó
Abstract: To evaluate the molecular interaction of recombinant horseshoe crab plasma lectin (rHPL) with Pseudomonas aeruginosa PAO1, multivalent rhamnobioside derivatives were designed. Eight rhamnoclusters with three or four α(1–3)‐rhamnobiosides attached to different central cores, such as methyl gallate, pentaerythritol, and N ‐Boc Tris, through either an ethylene glycol or a tetraethylene glycol linker, were assembled in two consecutive azide–alkyne cycloaddition click reactions. The synthetic method embraced the preparation of two α(1–3)‐rhamnobiosides with different linker arms and their conjugation, in stoichiometric or substoichiometric amounts, to propargyl ether‐functionalized tri‐ or tetravalent scaffolds. A divalent derivative and two self‐assembling rhamnobiosides were also prepared. The different architectures and valences of the rhamnoclusters provided an opportunity to evaluate the impact of topology and valency on the binding properties toward rHPL. Inhibitory ELISA data showed that all covalently linked rhamnoclusters could inhibit P. aeruginosa PAO1 recognition activity of rHPL with high efficacy. Trivalent rhamnobiosides showed a stronger inhibitory effect on P. aeruginosa PAO1 binding, and the more flexible clusters on a pentaerythritol or a Tris core were superior to the less flexible methyl gallate‐based clusters. Interestingly, the length of the linker arms had a very low impact on the binding ability of the rhamnoclusters. Herein, the two trivalent derivatives on an N ‐Boc protected Tris central core were the best inhibitors. The self‐assembling amphiphilic rhamnobioside derivatives were found to display no multivalent effect. Abstract : Less is sometimes more : Two sets of glycoclusters with up to four α(1–3)‐rhamnobiosides were prepared to study their inhibitory effect on recombinant horseshoe crab plasma lectin (rHPL)–bacteria interactions. Trivalent rhamnobiosides on a pentaerythritol or a Tris central core showed a stronger inhibitory effect on P. aeruginosa PAO1 binding than either the corresponding tetravalent derivatives or the less flexible methyl gallate‐based trivalent clusters (see figure).